The Role of Matrix Metalloproteinase9 (MMP9) in Endometriosis - Amalia, Amalia; Abdullah, Nusratuddin; Malinta, Umar (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To investigate the role of MMP-9 expression in endometriosis. Methods: The study was conducted from October 2015 to March 2016, an observational study with cross-sectional design. Samples are all endometriosis patients who underwent laparoscopic surgery in Dr. Wahidin Sudirohusodo Hospital and several other hospitals in Makassar. Samples were stored and fixed in the Grand Medika Histopathology Laboratory Makassar for examination the expression of MMP-9 using immunohistochemical methods. Conducted an analysis of 50 samples, of which 11 samples of stage II, 21 stage III samples, and 18 samples of stage IV. The data obtained and analyzed statistically using Mann Whitney and Chi Square test with a significance level of p <0.05. Results: The results reported rankings mean the expression of MMP-9 in stage I-II = 16.68, stage III-IV 27.99 (p = 0.013). There were differences in the expression of MMP-9 based on the stage. Stage I-II endometriosis had a more positive 2 expression of MMP-9 (45.5%), stage III-IV endometriosis have more positive 3 expression of MMP-9 (59.0%). The results of chi square test (p = 0.043). Conclusion: Higher expression of MMP-9 is significantly associated with higher degree of endometriosis. Keywords: matrix metalloproteinase-9, stages of endometriosis